Educational strategies to reduce the achievement gap: a systematic review - Cabral-Gouveia, Carmo; Menezes, Isabel; Neves, Tiago (Frontiers in Education, 2023)
Abstract Despite continuous efforts, the educational achievement gap is still, in most societies, a significant obstacle to ensuring more equity and social justice. Much of this inequality derives from belonging to historically discriminated groups. Indeed, coming from a lower socioeconomic status (SES), of an immigrant, or descendant situation, being Black, Hispanic, Gypsy, or any other racialized condition, still strongly influences academic attainment, school dropout and career choices. However, many innovative strategies and policies have been implemented to minimize this bias. This investigation proposes to gather, assess, and analyze these most recent interventions and perceive which of these present a better level of efficacy. Using the PRISMA guidelines, this Systematic Review of Literature yielded 30 studies that fit the inclusion criteria. The analysis considered the level of efficacy, intervention method and scope. Results show that targeted strategies, such as working on reading abilities and school subjects' focused interventions are more effective in improving minorities' and lower SES students' attainment. Other beneficial initiatives include whole-school, state and community-based projects, innovative pedagogies, and, finally, programs that deal with the psycho-social consequences of racism and discrimination, e.g., the internalization of negative perceptions and expectations. Overall, there is a strong need to develop mixed-method and longitudinal designs that will further our knowledge about what type of measure works, while considering a situated and contextual perspective, instead of a one-size-fits-all approach.